Promoting Religious based Tourism through Traditional Culinary Product Up-Scaling - Saadah, Mar Atun; Suri, Anggun; Rosa, Refa; Marpaung, Asnija Minarni (Jurnal Pengabdian UNDIKMA, 2025)
This community service aims to provide training and assistance in making business legality in the form of Halal Certificates (HC), Business Identification Numbers (BIN), and Household Industry Food License Numbers (HIFL) as an effort to support halal tourism in the Seberang Kota area. This service applied a Participatory Action Research (PAR) approach that emphasizes active participation from service participants to ensure the transfer of knowledge and skills. The participants of this activity consisted of 24 business actors who processed various superior products based on local potentials such as processed fish, shrimp, and tubers. We employed objective-oriented, management-oriented, and participant-oriented monitoring approaches. Furthermore, we applied the participatory evaluation method by involving the community, facilitators, and project team. The results of this community service showed that there was an increase in participants’ knowledge about the urgency of business legality, halal sharia provisions, and knowledge of the halal certification process. There is also a change in behavior from being unable to process legality to being able to access various online creation pages. At the end of the activity, the team submitted 24 BIN, HIFL, and CH documents.